METHODS FOR ASSESSING FACTORS AFFECTING THE EFFICIENCY OF SMALL BUSINESSES (Universal International Scientific Journal, 2026)
In this article, small businesses are presented as the most flexible and active part of the economic system in a market economy. They play an important role in increasing employment, creating new sources of income, and supporting regional development. Therefore, a scientific assessment of their activities is of particular importance in economic policy and management decisions.
Keywords: Assessment concept; assessment criteria; small business